2017
DOI: 10.4269/ajtmh.16-0470
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus in Southern Vietnam: Current Situation

Abstract: In Vietnam, there are no accurate data on tetanus incidence to allow assessment of disease burden or vaccination program efficacy. We analyzed age structure of 786 tetanus cases admitted to a tertiary referral center in Vietnam for three separate years during an 18-year period to examine the impact of tetanus prevention programs, namely the Expanded Program on Immunization (EPI) and the Maternal and Neonatal Tetanus (MNT) initiative. Most cases were born before the initiation of EPI. Median age increased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 11 publications
2
21
1
Order By: Relevance
“…Test results were found to be a more reliable predictor of where gaps in immunity led to outbreaks in 2014 than were national coverage data or data from the UNICEF Multiple Indicator Cluster Surveys or Demographic and Health Surveys ( 14 ). Similarly, samples from the OUCRU 13-site serum bank have been tested for tetanus antibodies in Ho Chi Minh City; the results showed gaps in immunity to tetanus, consistent with the observed age distribution of tetanus case-patients, which should be addressed by additional vaccination ( 31 ). …”
Section: Types Of Relevant Serosurveillance Collections Already Undersupporting
confidence: 59%
See 1 more Smart Citation
“…Test results were found to be a more reliable predictor of where gaps in immunity led to outbreaks in 2014 than were national coverage data or data from the UNICEF Multiple Indicator Cluster Surveys or Demographic and Health Surveys ( 14 ). Similarly, samples from the OUCRU 13-site serum bank have been tested for tetanus antibodies in Ho Chi Minh City; the results showed gaps in immunity to tetanus, consistent with the observed age distribution of tetanus case-patients, which should be addressed by additional vaccination ( 31 ). …”
Section: Types Of Relevant Serosurveillance Collections Already Undersupporting
confidence: 59%
“…Convenience sampling introduces bias because the sampled population may not be representative. However, this type of sampling is less expensive and easier to undertake and therefore can be conducted more regularly and may still provide relevant information, as has been illustrated for measles and tetanus in Vietnam ( 14 , 31 ). …”
Section: Collection Types and Their Pros And Consmentioning
confidence: 99%
“…The Fourier transform for the frequency-domain features (f l and f w ) pose a computational cost of O(L log (L)) associated with the FFT computation. In addition, we provide (1). The number of patients per class is shown in brackets.…”
Section: Complexity Analysismentioning
confidence: 99%
“…Tetanus is a severe disease, often necessitating lengthy hospital treatment (up to six weeks), which was estimated to have caused 48-80,000 deaths in 2015 [2]. It tends to affect the poorest in society in lowand middle-income countries where unvaccinated individuals, particularly manual workers and farmers, are at high risk of contracting it [1,[3][4][5]. A recent study showed that tetanus prevalence is still high in a part of Asia and that it is associated with high morbidity and mortality rates [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Infectious diseases, such as tetanus and hand, foot and mouth disease (HFMD), can still be life-threatening conditions for patients in low and middle income countries [1]. Tetanus often affects the poorest in society in low and middle income countries, and it was estimated to have caused 48-80,000 deaths in 2015 [1]- [4]. Tetanus cases can progress to severe conditions in many cases, and the subsequent hospital treatment is often lengthy (up to six weeks).…”
Section: Introductionmentioning
confidence: 99%